ANALISIS BEBERAPA VARIABEL FUNDAMENTAL YANG MEMPENGARUHI STRUKTUR KEUANGAN DAN IMPLIKASINYA TERHADAP RENTABILITAS EKONOMI - Wiwiek Kusumaning Asmoro (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2012)
This study aimed at determining influence of sales growth rate, assets structure, and company’s size and retained earning variables on Financial Structure and Earning Power. Sampler used in this study consist 68 food’s beverages companies that listed their shares on Indonesia Stock Exchange. Sampling techniques used in this study is purposive sampling, judgemental sampling type? Collection data’s used documentation techniques with pooled directory from IDX corner. Analysis method used in this study is multiple regression analysis, recursive model with a = 0, 05. Analysis indicated that at first equation sales growth rate, assets structure, company’s size, and retained earning variables had significant influence simultaneously on financial structure. It was proved with (sig F = 0,000 < a = 0, 05). Retained earning variable had dominant influence on Financial Structure (this variable had biggest t & B and smallest sig). At second equation, sales growth rate, assets growth rate, assets structure, company’s size, retained earning; variables simultaneously had significant influence on Earning Power. Retained earning variable is dominant variable influenced Earning Power. Determinant coefficient of first equation is 0,271 or 27,1% and second equation is 0,650 or 65%.